Organizational capacity as potential moderator in enhancing corporate performance: a proposed framework - Mustapa, Ifa Rizad; Abdul Malak, Siti Seri Delima (Asia Pacific Institute of Advanced Research (APIAR), 2017)
In line with the introduction of the Malaysian Code on Corporate Governance (MCCG) in 2000, companies that comply with the recommendation of the MCCG which stresses on accountability and transparency, is expected to perform better than others.Looking further on issues associating to industries, recent studies proved that organizational capacity, which is understood as developing the resources and capabilities of an organization that are valuable, rare, imperfectly imitable and non-substitutable that generates particular organizational tendencies to create competitive advantages and disadvantages, form part of the organization’s environment that affect its performance (Camison & Villar-Lopez, 2014; Chen, Qiao & Lee, 2014; Dowdell, Herda & Notbohm, 2014). Recognizing its importance to the industry, the current study intends to examine the moderating effect of organizational capacity on the association between corporate governance and corporate performance in Malaysia since no prior studies have reported on the work albeit they examined the influence of these variables independently (Tayles, Pike & Sofian, 2007; Abdullah, Lall & Tatsuo, 2008; Khong & Eze, 2008; Fatt, Khin & Heng, 2010; Hussein et al., 2014). A questionnaire survey and the regression analysis methods will be applied in obtaining the data and answering the research questions respectively. The outcome of this research is expected to contribute to the industry by identifying of whether organizational capacity plays a significant role in moderating the association between corporate governance and corporate performance and hence acknowledge firms of how they can improve their performance through organizational capacities.